Presentation and Management of Thyroid Involvement in Systemic and Primary Thyroid Lymphoma: A Case Series - Marcos Tadashi Kakitani Toyoshima; Camila Regina Pereira Batista de Macedo; Isabelle Pinheiro Amaro de Magalhães; Rodrigo Dolphini Velasques; Ana O. Hoff (Annals of Internal Medicine: Clinical Cases)
This case series describes 4 female patients with thyroid lymphoma, including 3 primary thyroid lymphomas and 1 secondary thyroid involvement due to Burkitt lymphoma. Identified within a cohort of 878 lymphoma patients (2018–2022), primary thyroid lymphomas represented a 0.5% prevalence. Cervical ultrasound, computed tomography, or magnetic resonance imaging revealed thyroid abnormalities. Fine-needle aspiration biopsy followed by biopsy confirmed diagnoses. Positron emission tomography with 18F-fluorodeoxyglucose (FDG-PET) highlighted metabolic activity correlating with aggressiveness. This series emphasizes the complementary roles of imaging and pathology in diagnosis and highlights the importance of a multidisciplinary approach to managing these rare malignancies.